EXEMPTION OF SERVICEMEMBERS FROM CRIMINAL LIABILITY: ISSUES AND PROSPECTS OF IMPLEMENTATION - Piskun, Ivan; Tretiakov, Dmytro (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
The purpose: the purpose of this study is to conduct a comprehensive analysis of newly introduced legislation that allows for the exemption of servicemembers from criminal liability, provided they voluntarily return to their military unit and obtain the commander’s written consent, as well as to identify the main challenges and prospects for implementing this mechanism. Research methods: the study employed legislative analysis (focusing on the Criminal Code of Ukraine, the Criminal Procedure Code of Ukraine, and relevant subordinate legal acts), content analysis of scholarly literature, and systematic-structural and comparative-legal approaches. These methods were used to assess the effectiveness of the new liability-exemption mechanism and to minimize corruption risks. Results: the article elucidates the legal essence of the recently enacted changes, particularly the introduction of additional grounds for exempting servicemembers who have committed offenses specified in Articles 407–408 of the Criminal Code of Ukraine. Special attention is paid to the pivotal role of the military unit commander’s written consent, noting the absence of formalized criteria for granting such consent - an omission that carries a risk of subjectivity. The study highlights potential corruption risks and proposes avenues for improving legislation, including the development of detailed subordinate regulations and the establishment of appeal procedures in cases where a commander refuses to provide consent. Discussion: while these legislative innovations could serve as an effective instrument for retaining personnel and incentivizing the voluntary return of servicemembers who have committed certain offenses, the significant reliance on the commander’s discretion calls for precise regulatory guidance and oversight. Such measures would help prevent corrupt practices and safeguard the principle of equality before the law.